Morphometric analysis of the pigmentation in colombian species of Drosophila (Diptera: Drosophilidae) from the repleta group - PRIETO-S., RODRIGO; DE POLANCO, MARÍA MAGDALENA E. (Revista Colombiana de Entomología, 2009)
The abdominal pigmentation of geographically isolated populations of species of the repleta group, D. martensis, D. starmeri and D. uniseta (martensis cluster), was compared. Our purpose was to detect whether the distance that separated them, together with the environmental heterogeneity, are related to a process of geographic race formation. Moreover, variation in the aforementioned character was compared between D. aldrichi from the mulleri cluster, and species from the martensis-cluster species, attempting to contrast the evolutionary relationships among these species. The outline of the third-abdominal spot was digitalized with elliptic Fourier descriptors and multivariate canonical analysis for the four populations collected from Camarones (Riohacha-Guajira Department), Santa Marta (Magdalena Department) and Rosalía (Tatacoa Desert, Huila Department). Results showed significant differences in the form of the abdominal spot morphology among the species (P